Stylistic analysis of election campaign visuals in the secure and intensely competitive constituencies of the 2021 Sarawak State Election - Siti Haslina, Hussin; Malia, Taibi; Ammar Redza, Ahmad Rizal (Taylor's University, 2024)
This study analysed election campaign visuals in the secure and intensely competitive constituencies of Kuching and Kota Samarahan during the 2021 Sarawak State Election. Using Crystal and Davy’s (1969) framework of stylistic analysis and Benoit’s (2017) functional theory of political campaign communication, 20 posters and 12 banners were analysed to examine their graphetic, typographical and textual features. Findings show that graphetically, the campaign visuals in secure constituencies often used images to acclaim past achievements while those in intensely competitive constituencies reflected the electorate’s dissatisfaction to attack. Typographically, the campaign visuals in the secure constituencies only used capitalisation whereas those in intensely competitive constituencies used capital letters, questions marks, and exclamation marks. Analysis of textual choices reveals the presence of explicit messages in phrasal form in the election posters and banners in both the secure and intensely competitive constituencies. Semantically, the ambiguous messages in the intensely competitive constituencies were personal, emotive, subjective, and ambiguous but those in secure constituencies were largely literal and declarative to reflect the confidence level of the political parties in winning the election based on their track record. The findings indicate that the intensity of the electoral fight is reflected in the visual and textual images of campaign visuals. Keywords: Stylistic analysis, election posters, election banners, Sarawak, Malaysia